Host plant volatiles induce oriented flight behaviour in male European grapevine moths, Lobesia botrana - von Arx, M.; Schmidt-Busser, D.; Guerin, Patrick (My University, 2011)
The European grapevine moth Lobesia botrana relies on a female produced sex pheromone for long-distance mate finding. Grapevine moth males compete heavily during limited time windows for females. The aim of this study was to investigate the perception of host plant volatiles by grapevine moth males and whether such compounds elicit upwind oriented flights. We compared five host plant headspace extracts by means of gas chromatography linked electroantennogram (EAG) recording. We identified 12 common host plant volatiles (aliphatic esters, aldehydes, and alcohols, aromatic compounds and terpenes) that elicit EAG responses from grapevine moth males and that occur in at least three of the host plant volatile headspace extracts tested. Subsequently the behavioural response of grapevine moth males to four these compounds presented singly and in mixtures (1-hexanol, 1-octen-3-ol, (Z)-3-hexenyl acetate and (E)-beta-caryophyllene) was recorded in a wind tunnel. Grapevine moth males engaged in upwind flights to all of four compounds when released singly at 10,000 pg/min and to all, except 1-octen-3-ol, when released at 100 pg/min. A blend of the four host plant volatiles released at 10,000 pg/min and mixed at a ratio based on the analysis of Vitis vinifera cv. Solaris volatile emissions attracted significantly more males than any single compound. Grapevine moth males perceive and respond to host plant volatiles at biologically relevant levels indicating that host plant volatiles figure as olfactory cues and that L botrana males can discern places where the likelihood of encountering females is higher. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: lobesia botrana; european grapevine moth; host plant volatiles; electrophysiology; wind tunnel; tortricidae; sex-pheromone; codling moth; eupoecilia-ambiguella; phytophagous insects; apple volatiles; cydia-pomonella; nonhost plant; floral scent; wind-tunnel; fruit moth